2022
DOI: 10.3389/fimmu.2022.927565
|View full text |Cite
|
Sign up to set email alerts
|

A tumor microenvironment-related risk model for predicting the prognosis and tumor immunity of breast cancer patients

Abstract: BackgroundThis study aimed to construct a tumor microenvironment (TME)-related risk model to predict the overall survival (OS) of patients with breast cancer.MethodsGene expression data from The Cancer Genome Atlas was used as the training set. Differentially expressed gene analysis, prognosis analysis, weighted gene co-expression network analysis, Least Absolute Shrinkage and Selection Operator regression analysis, and Wald stepwise Cox regression were performed to screen for the TME-related risk model. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…For example, new findings indicate that the diversity in the hierarchical malfunction of T-cell exhaustion can have an effect on the prognosis of cancer, offering the potential to utilize it as a reliable predictor of outcomes in cancer patients [ 41 ]. The newly developed and robust tumor microenvironment-related risk model had significant implications for breast cancer patients in terms of overall survival [ 42 ]. Tumor-infiltrating immune cells are vital components of the tumor microenvironment, actively contributing to both the response to tumor therapy and the progression of tumors [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, new findings indicate that the diversity in the hierarchical malfunction of T-cell exhaustion can have an effect on the prognosis of cancer, offering the potential to utilize it as a reliable predictor of outcomes in cancer patients [ 41 ]. The newly developed and robust tumor microenvironment-related risk model had significant implications for breast cancer patients in terms of overall survival [ 42 ]. Tumor-infiltrating immune cells are vital components of the tumor microenvironment, actively contributing to both the response to tumor therapy and the progression of tumors [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an extensive review of the pertinent literature from the past ve years was conducted. Subsequently, 18 signature genes associated with diverse biological processes, including exosome (13,14), TP53 mutation (15), necroptosis(16), depression (17), pyroptosis(18), autophagy (7,19), immune (20)(21)(22), angiogenesis (23), cuproptosis(18, 20), tumor microenvironment (TME) (24), methylation (25), natural killer cell (26), lipid metabolism (27), were incorporated for comparative analysis. The mlMSG prognostic model exhibited superior C-index performance compared to nearly all models present in TCGA and GEO datasets (Fig.…”
Section: Construction Of Prognostic Models Of Mlmsgsmentioning
confidence: 99%
“…[10,11] For example, it was reported that the context of TME such as the numbers of CD8 + T cells, CD4 + T cells, tumor-associated macrophages, dendritic cells, natural killer cells, and so forth, closely correlates to the prognosis of a variety of malignant tumors including lung cancer, gastric cancer, breast cancer, liver cancer and as well as glioma. [12][13][14][15] The latest research indicated how cancer cell disrupts the microenvironment in the normal stroma and promotes initiation, proliferation, invasion, metastasis, and angiogenesis in glioma development. [16] It is feasible to suppose that TME might link to the clinical outcome of glioma.…”
mentioning
confidence: 99%